PENERAPAN ANALISIS KLASTER METODE WARD TERHADAP KABUPATEN/KOTA DI JAWA TENGAH BERDASARKAN PENGGUNA ALAT KONTRASEPSI - Yogi Isna Hartanto; Agus Rusgiyono; Triastuti Wuryandari (Jurnal Gaussian, 2017)
The cluster analysis of the Ward method is a cluster forming method based on minimizing the loss of information due to the incorporation of objects into clusters. An Error Sum of Square (ESS) is used as an objective function. Two objects will be combined if they have the smallest objective function among possibilities. The similarity measure used is the Euclidean distance. In this experiment used data from the number of users of contraceptives in Central Java Province. Contraceptives that can be detected its use is IUD, MOW, MOP, condoms, implants, injections, and pills. The results of cluster analysis of Ward method were obtained as many as 3 clusters. First cluster consists of 9 districts/cities with the number of use of most contraceptives, namely Cilacap, Banyumas, Pati, Pemalang, Tegal, Jepara, Grobogan, Demak, and Semarang City. Second cluster consists of 21 districts/cities with the number of use of medium contraceptives, namely Purbalingga, Banjarnegara, Kendal, Wonogiri, Pekalongan, Blora, Brebes, Kebumen, Wonososbo, Boyolali, Karanganyar, Sragen, Magelang, Klaten, Semarang, Purworejo, Temanggung , Sukorejo, Rembang, Batang, and Kudus. Third cluster consists of 5 districts/cities with the number of use of contraceptives a little, namely Magelang City, Salatiga City, Surakarta City, Pekalongan City, and Tegal City. Keywords: Contraceptives, Cluster Analysis, Ward Methods, Euclidean Distance